2016
DOI: 10.2147/opth.s122542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3% diquafosol sodium ophthalmic solution on higher-order aberrations in patients diagnosed with dry eye after cataract surgery

Abstract: PurposeTo evaluate the effects of diquafosol sodium ophthalmic solution 3% (DQS) and artificial tears (AT) on higher-order aberrations (HOAs) in patients with dry eye after cataract surgery.DesignThis was a post hoc analysis of a previously conducted randomized clinical study.MethodsFifty-nine eyes from 42 patients (17 males and 25 females, aged 72.6±8.0 years) with verified or suspected dry eye at 4 weeks after cataract surgery were evaluated. The dry eye patients were randomly assigned to receive DQS or AT f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…Together, 3 studies [ 15 , 20 , 21 ] included 133 eyes in the DQS group and 144 eyes in the AT group described the BUT before the treatment of postoperative dry eye. When pooling the data of pretherapeutic BUT, fixed-effect models were used as Chi-squared test manifested no heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Together, 3 studies [ 15 , 20 , 21 ] included 133 eyes in the DQS group and 144 eyes in the AT group described the BUT before the treatment of postoperative dry eye. When pooling the data of pretherapeutic BUT, fixed-effect models were used as Chi-squared test manifested no heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Four papers [ 15 , 20 22 ] described the post-therapeutic BUT, including 178 eyes in DQS group and 193 patients in AT group. Sensitivity analysis and subgroup analysis failed to eliminate the detected heterogeneity ( P = .056, I 2 = 60.3%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous investigation, using sequential wavefront measurements, revealed that diquafosol was effective for treating dry eye after cataract surgery, with prolonged BUT and improved optical quality. An upward pattern in HOAs after the blink observed before the cataract surgery shifted to a stable pattern after the 4-week treatment with diquafosol 56. Rebamipide was effective for improvement of optical quality and BUT in cases of short BUT-type dry eye 57…”
Section: Quality/quantity Of the Tear Film And Qov: Dry Eyementioning
confidence: 96%